Studi ilmu pendidikan Islam / Moh. Haitami Salim & Syamsul Kurniawan ; editor, Rose Kusumaning Ratri. - HAITAMI SALIM, Moh., 1965-; Syamsul Kurniawan; Rose Kusumaning Ratri (Ar-Ruzz Media, 2012)
287 hlm. ; 21 cm (3 eks.)